REGIONAL DISPARITIES IN LABOUR PRODUCTIVITY AND THE ROLE OF CAPITAL STOCK. (August 2020) - Gardiner, Ben; Fingleton, Bernard; Martin, Ron
Abstract : This paper reports on the availability of regional capital stock data, 1 in the form of new/updated regional (NUTS2 level) capital stock estimates, 2 building on an approach (Perpetual Inventory Method) which had been previously developed for the European Commission. The particular focus here is on the UK and how these data are used to shed light on regional labour productivity disparities. Using a NUTS2 level dataset constructed for the period 2000–16, we use a dynamic spatial panel approach from Baltagi et al . (2019) to estimate a model relating productivity to output (growth or levels) and augmented by explicit incorporation of capital stock plus various other covariates such as human capital. We find that regional variations in capital stocks per worker make a significant contribution to regional variations in labour productivity, but the geography of human capital is also highly relevant. Moreover, we give evidence to show that as human capital rises, notably as we move from the regions to London, the impact of capital stock per worker is less. The effect of capital stock depends on the level of human capital.